EXPLORING THE INFLUENCE OF BRAND AWARENESS ON PURHCASE INTENTION: THE ROLE OF PERCEIVED QUALITY AND BRANDS ASSOCIATIONS IN THE INTERACTIVE ENTERTAINMENT MERCHANDISE MARKET - Sylvia Samuel; Daniel Widjaja (Faculty of Economics and Business Universitas Pelita Harapan, 2026)
This research was conducted to determine the effect of Brand Awareness on Purchase Intention for HoYverse Merchandise, with Perceived Quality and Brand Association as mediators. The method used in this study is PLS-SEM to identify relationships among existing variables. The PLS-SEM method is well-suited for analyzing research involving multiple variables and causal relationships, with results remaining effective even when the available data do not meet the normal distribution assumption. The data for this study were obtained from questionnaires completed by 350 respondents, including fans and individuals familiar with the HoYoverse brand. Based on the data analysis, brand awareness and perceived quality significantly affect purchase intention, while the other variables also exert significant effects. The results of this study indicate that an effective marketing strategy is not only through how well a brand is known or the perception of product quality in the context of the interactive entertainment industry offering merchandise. Therefore, it is hoped that this research can serve as a reference for companies to optimize their marketing strategies and for future researchers to explore other relevant variables.